복부초음파검사로 진단된 담낭용종의 유병률과 위험인자 분석 - 이미화(Mi Hwa LEE); 조평곤(Pyong Kon Cho); 권덕문(Duck Moon Kwon) (방사선기술과학, 2015)
This study was designed to determine the prevalence of gallstones in the last three years and evaluate the associated risk factors in the population who underwent health screening. Although there are many studies reporting the prevalence and risk factors of GB polyp, the results varied among each report. The aims of this study were to evaluate the prevalence rate and risk factors of GB polyp, colon polyp and fatty liver in the population who underwent health screening. The study population consisted of 4,877 visited the health promotion center in Dalseogu, Daegu in Korea from January 2011 to December 2013. Each participant in the study had their biliary system gallbladder examined using ultrasonography. The prevalence of GB polyp was evaluated along with age, gender, metabolic syndrom, body mass index (BMI), Fatty liver, Colon polyp. A showed of total 383 (7.9%) people were found to have GB polyps. The prevalence of sex among 256 (9.8%) patients men and 127 (5.6%) women which showed significantly higher in male than in female subjects(p=0.001). The mean size of the GB polyps 4.92 mm (1.6-17 mm). The sizes of most GB polyps (73.6%) were less than 10 mm in diameter. 122 subjects (31.28%) had multiple GB polyps which 2 or more polyps and 261 subjects (68.2%) had single polyp. Independent risk factors related with GB polyp were male gender (OR 0.551, p<0.001), overweight that BMI above $23kg/m^2$ (OR 0.713, p=0.002) triglyceride (OR 0.571, P<0.001), metabolic syndrome (OR 0.049, p=0.033) and colon polyp (OR 1.409, p=0.002). In spite of the conclusion, the prevalence GB polyp was higher than previous Korea and other country reports. The GB polyp in a healthy population was results as 7.9%. The risk factors of GB polyps were found to be male, being overweight, triglyceride, metabolic syndrome and colon polyp. Not only the subject of a health examination is needed but, a further study of the general public when possible. 인구 고령화에 따른 암에 대한 관심 증가로 건강 검진을 받는 수검자가 늘고 있으며, 담낭용종의 유병률과 체질량 지수, 성별, 나이, 대사증후군 등의 위험인자에 대한 몇몇 연구가 있으나 본 연구는 최근 3년간의 담낭용종의 유병률과 대장용종 유무, 지방간 등의 다른 위험인자를 알아보고자 하였다. 2011년 1월에서 2013년 12월까지 대구지역 종합검진전문병원에서 건강검진을 받은 4,877명을 대상으로 성별과 나이를 조사하고, 키, 몸무게, 공복혈당, 간기능 및 기본 지질검사를 하였다. 복부초음파검사를 통해 담낭용종을 진단하고 지방간, 대장 내시경 결과 용종의 유무를 분석하였다. 분석결과 담낭용종이 발견된 경우는 383명(7.9%)으로 남자 256명(9.8%), 여자 127명(5.6%)으로 남자에서 담낭용종 유병률이 의미 있게 높았다(p<0.001). 연령별 담낭용종 유병률은 40대에서 3.50%로 가장 높게 나타났고 유의하게 나타나지 않았다. 담낭용종 크기는 평균 4.92 mm (1.6-17 mm)로 10 mm 이하가 73.6% 나타났다. 383명 중 261명(68.2%)이 단발성 용종, 122명(31.28%)이 2개 이상의 다발성 용종으로 타나났다. 남성 (OR 0.551, p<0.001), 과체중 (OR 0 .713, p=0.002), 중성지방 (OR 0 .571, p<0.001), 대사증후군 (OR 0 .049, p=0.033), 대장 용종 유무 양성 (OR 1.409, p=0.002)등이 담낭용종 발생에 영향을 미치는 독립인자로 선정되었다. HBsAg 양성은 담낭용종 발생에 관련 있는 위험인자가 아니었다. 결론적으로 본 연구는 담낭용종이 유병률은 과거보다 높은 7.9%로 나타났다. 남성, 과체중, 중성지방, 대사증후군, 대장용종이 담낭용종의 위험인자였다. 향후 건강검진 수검자 대상뿐만 아니라 일반국민을 대상으로 추가적인 검사가 필요하다고 사료되고, 담낭 절제술을 받아서 조직학적으로 확인된 경우를 조사 할 필요가 있겠다.